Had An Effect Of Debt Equity Ratio, Return On Assets, Firm Size, Earnings Per Share, Cash Position And Total Asset Turnover on Dividend Payout Ratio in Manufacturing Companies - Harahap, Qori Nurul Hasanah; Toni, Nagian; Simorangkir, Enda Noviyanti (UNIVERSITAS PAKUAN, 2022)
The purpose of this study is to examine the effect of DER, ROA, Firm Size, EPS, Cash Position and Total Asset Turnover using the t test and F test. This research uses descriptive quantitative. The number of manufacturing companies used as a population is 169 companies selected based on purposive sampling obtained a sample of 54 companies. The data analysis technique used is multiple linear regression analysis. The results of data analysis show that partially only DER has a significant negative impact on DPR. Simultaneously, six independent variables have a significant impact on DPR. The coefficient of determination test results show the Adjusted R Square number 0.108, which means that 10.8% of the variation of DPR of manufacturing companies can be explained by the independent variables used, the remaining 89.2% is caused by other factors such as Growth Opportunity, Ownership, Current Ratio and others.